Pengaruh Kompetensi Pedagogik Terhadap Hasil Belajar Siswa Setingkat MI - Wanda Citra Dewi; Didit Darmawan (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This literature study examines the influence of pedagogical competence on the learning outcomes of Madrasah Ibtidaiyah (MI) in Indonesia. The teacher's effort in carrying out a task well, a teacher or lecturer must have high pedagogical competence in order to achieve educational goals. Teaching and learning process activities can be designed well if there are already educational goals, learning content, learning methods, learning media, and other educational elements, as well as a good relationship between students and teachers. This research applies literature by deciphering from various aligned academic sources. Research results show that teachers or educators really need pedagogical competence to develop student learning experience and streamline the learning process at Madrasah Ibtidaiyah.